Implementasi Konsep Pendidikan Karakter Ki Hajar Dewantara Berbasis Nilai-Nilai Pancasila Bagi Mahasiswa Generasi Mileneal - Sigit Sapto Nugroho; Mohammad Choirul Anam; Mochammad Juli Pudjiono; Mudji Rahardjo; Bambang Sukarjono (Universitas Merdeka Madiun, 2020)
Abstractâ€” Pancasila as the state ideology is the basic reference for all Indonesian citizens in various sectors of life. However, the fact is that currently the noble values of Pancasila are increasingly being eroded due to the influence of globalization and the rapid progress of science, technology and art which are not well filtered. To restore the value of Pancasila in the life of society, nation and state, it is necessary to implement the values of Pancasila based on character education. The purpose of writing this scientific paper is to discuss the values of national character based on Pancasila and the concept of character education based on Pancasila values for millennial generation students. The data collection method used was literature review with descriptive-critical analysis techniques. Based on the results of the research, it shows that the values contained in the Pancasila ideology can be used as a basis for character education for students, especially the millennial generation, which in its implementation uses the concept of character education from Ki Hadjar Dewantara which includes the Among and Tri-Nga systems based on the educational Tripusat, namely family, school and community.Â Keywordsâ€”: Pancasila Values; Character Education; Milineal Students dispute.